PUBLICANS ACCORDING TO THE JUSTINIAN’S DIGEST – INSTITUTIONALISED CORRUPTION AND ITS LEGAL SANCTIONING - Deretić, Nataša; Milutin, Milan M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Rapid expansion of ancient Roman territory was apparently not followed by a sufficiently quick growth of public administration. Consequently, a part of public authorities was entrusted to private individuals. This process appeared to be mutually beneficial. Public authority achieved the implementation of its jurisdiction, tax collection being of particularly significant importance, while publicans, private individuals, acquired vast profits. Their profits were often a consequence of their abuse of the public authorities entrusted to them. The profit growth was followed by a growth of publicans’ power and influence within the society, and consequently, the possibility of holders of public authorities to bring them to justice by exercising their powers was limited. Nevertheless, the aspect of legal limitations of publicans in which the authorities were partially successful, refers to the circumstances in which the public interest was harmed. Private individuals, however, were largely left at the mercy of the illegal actions of the publicans. The texts of Justinian’s Digest, thus originating form the classical period, in which these matters are considered, were analysed in this paper.
Keywords: publicans, corruption, abuse of public authority, public finance, sanctions